Gravity for Geodetic Purpose: Geoid-Ellipsoid Separation and Orthometric Height System - KC, Shanker (Journal on Geoinformatics, Nepal, 2019)
Gravity plays very crucial role in geodetic issues as gravity field determines the shape of the earth. This paper reviews – beginning from defining the gravity, various applications of gravity in geodesy and in other fields, nature of gravity field of our terrain, instruments of gravity measurement, and techniques of gravity survey. This paper first gives information about gravity networks in Nepal, presents an equation to compute orthometric correction (OC) from height obtained from levelling. Gravimetric geoid-determination method is explained here with various gravity reduction methods and topographic-isostatic gravity reduction method is recommended for N- separation computation as this method results gravity anomalies near to zero.